PERAN DINAS PARIWISATA DAN KEBUDAYAAN KOTA PADANG DALAM MENINGKATKAN WISATA MICE DI KOTA PADANG - Romaduti Sari Nurillah; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
MICE (meeting, incentive, convention and exhibition) is a a type of tourism activity which is a large group, usually carefully planned, set off together for a particular purpose. Role is a behaviors that are expected to be performed by someone who occupies a particular position, either in the organization's position or in the state's stance. Every person who occupies that position, is expected to behave in accordance with the nature of that position. The research was conducted at the department of tourism and culture of Padang city, which is located at Gandaria street number 56, Padang. Department of tourism and culture of Padang city selected as a research site for the department of tourism and culture is one of the government agencies working in the field of tourism. This research aims to determine the role of the department of tourism and culture of Padang city in improving the MICE in the Padang city. This research uses qualitative descriptive method to process the data obtained in the field through interviews, all the information collected and studied to become a unified whole (Kusuma and Sugiono 2000). Data collection techniques used were observation, interview, literature study and documentation. Based on the results of research that has been done the role of tourism and culture of Padang city in improving MICE with variable motivator, facilitator and dynamicator with good research conclusions.Keywords : meeting, incentive, convention and exhibition